2017
DOI: 10.1007/s00348-017-2446-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pressure fields in a swirling annular jet flow

Abstract: azimuthal velocity component also reaches peak values as a result of the inward motion of the fluid and the conservation of angular momentum. The POD analysis of the pressure fields suggests that the precessing helical vortex formation is the dominant coherent structure in the instantaneous flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Recently, clear evidence of a double-helical structure has been identified in the flow field of the same annular jet flow in both the velocity and pressure fields (Percin et al 2017;Vanierschot et al 2018). This double helix has the same features as the singlehelical PVC found in numerous other round or annular swirling jets: its branches are winded in the counter-swirl direction and the helix itself precesses along the central axis in the swirl direction.…”
Section: Coherent Structure Extractionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, clear evidence of a double-helical structure has been identified in the flow field of the same annular jet flow in both the velocity and pressure fields (Percin et al 2017;Vanierschot et al 2018). This double helix has the same features as the singlehelical PVC found in numerous other round or annular swirling jets: its branches are winded in the counter-swirl direction and the helix itself precesses along the central axis in the swirl direction.…”
Section: Coherent Structure Extractionmentioning
confidence: 81%
“…However, considering the frequency spectra of the temporal coefficients of these four pairs (figure 4), not one single but several distinct peaks are present. For instance the peak found at St = 0.27 in the studies of Percin et al (2017) and Vanierschot et al (2018) can be found in mode pairs II and III. This indicates that contributions from several different structures in the flow with their own dynamics are present in a single mode pair.…”
Section: Coherent Structure Extractionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some cases, the precessing is weak, whereas in others, it is coupled with strong velocity and pressure fluctuations [7,[19][20][21][22][23][24][25][26][27]. The phenomenon of the precessing vortex core (PVC) has been studied extensively for different swirling flow 3 configurations, including swirling jets.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, aero-engine combustors have been experimentally investigated through POD decomposition techniques. Based on the PIV measurements, the presence of a Vortex Breakdown Bubble (VBB) and a Precessing Vortex Core (PVC) have been partially revealed and characterised in strongly swirling jets using modal decomposition analysis both in non-reacting [155][156][157][158][159][160][161][162] and reacting [45,[163][164][165][166] conditions. Nevertheless, as a consequence of experimental diagnosis shortcomings (e.g., the sampling frequency of the Stereo PIV system can be sometimes much smaller than the PVC frequency [157]), temporal and spatial-detailed CFD simulations have emerged as a potential tool to successfully characterise the coherent structures within the combustor through pressure, vorticity and species signals decomposition rather than dealing just with velocity.…”
Section: Studies Based On Advanced Spectral Analysismentioning
confidence: 99%